The distribution of charges on the verge of substances of different nature - Зубченко, О.М.; Павлюх, Л.І. (Proceedings of National Aviation University (archive), 2008)
In article discrete distribution of plentiful charges on the electrode surfaces and features of structure of electrical field near the electrode surface is considered.